Preoperative Surgical Site Hair Removal for Elective Abdominal Surgery: Does It Have Impact on Surgical Site Infection - Dhamnaskar, Suchin; Mandal, Sumit; Koranne, Mandar; Patil, Pratik (The Surgery Journal, 2022)
Introduction Postoperative surgical site infection (SSI) forms the major burden of nosocomial infections in surgical patients. There is prevalent practice of surgical site hair shaving as a part of preoperative preparation. There is uncertainty regarding the benefit versus harm of shaving for SSIs. Hairs at surgical sites are removed prior to surgery most often by shaving. We performed this study to look for what impact preoperative hair removal by shaving has on postoperative SSI.Methods We performed prospective comparative cohort study in patients undergoing elective abdominal surgeries. We included clean and clean-contaminated surgeries in immunocompetent patients of which half were shaved and other half not shaved prior to surgery. Other confounding factors like skin cleaning, aseptic technique of surgery, antibiotic prophylaxis and treatment, and postoperative wound care were as per care. Patients were assessed for presence and grade of SSI postoperatively on day 7, 14, and 30. Results were analyzed statistically using chi-square and Fischer's exact tests for significance in entire sample as well as in demographic subgroups.Results Overall SSI rate was 11.42%. There was no statistically significant difference in SSI rates between patients who underwent preoperative surgical site hair removal by shaving (232) and who did not have shaving (232) on all the three different assessment timelines in postoperative period, namely, day 7, 14, and 30. Although the absolute number of patients who had SSI was more in those who underwent preoperative surgical site hair removal by shaving, the difference was not statistically significant (p > 0.05). But on subgroup analysis patients with clean-contaminated surgeries (p = 0.037) and patients with surgeries lasting for less than 2 hours (Fischer's exact = 0.034) had significantly higher SSI in the shaved group compared with unshaved on day 14.Conclusion As per our results, preoperative shaving did not significantly increase overall SSI except in subgroup of clean-contaminated surgeries and in surgeries of less than 2 hours' duration. So especially in these patients avoiding preoperative surgical site hair shaving may be used as one of the infection control measures.
Keywords: preoperative hair shaving; surgical site infection; elective abdominal surgery